The importance of frequency–place mismatch in the quality of sound perceived in single-sided deafness among cochlear implant recipients - Gersdorff, Guillaume; Ivanovic, Nicola; Zoka Assadi, Masoud; Nopp, Peter; Camby, Séverine; Lefèbvre, Philippe (Frontiers in Audiology and Otology, 2025)
IntroductionSingle-sided deafness (SSD) affects the ability to localize sounds and understand speech in noisy environments, significantly impacting the quality of life. Cochlear implants (CIs) have been explored as a solution for SSD, with varying success attributed to different factors, such as onset of deafness (pre- vs. post-lingual), duration of especially pre-lingual deafness, and compliance to rehab protocols, as well as the frequency-to-place mismatch, where the frequency assigned to CI electrodes does not align with the cochlea's natural tonotopy. The objective is to investigate the influence of frequency-to-place mismatch on hearing performance, sound quality, and patient satisfaction in SSD CI recipients by comparing default and anatomical frequency mapping.MethodsA retrospective study was conducted on 19 SSD patients implanted with MEDEL CIs between 2014 and 2023. Post-activation, high-resolution cone beam computed tomography scans were analyzed using OTOPLAN® (Version V4) to define anatomical frequency mapping. The average frequency mismatch (AFM) between default and anatomical mapping was calculated. Speech intelligibility was assessed using articulation function (AF) scores, and sound quality was evaluated through patient questionnaires.ResultsA significant negative correlation between AFM and AF (R = −0.47, p = 0.042) was observed. Sound quality aspects, including natural sound perception and similarity to the normal ear, inversely correlated with AFM (R2 = 0.281, p = 0.05, and R2 = 0.301, p = 0.043, respectively). Global satisfaction scores were high (3.58 ± 0.77), unaffected by AFM.ConclusionFrequency-to-place mismatch impacts speech intelligibility and sound quality in SSD CI patients. Anatomical frequency mapping using tools like OTOPLAN can enhance CI outcomes, highlighting the need for individualized cochlear measurements and electrode assignment.